(untitled) (Bangladesh Journal of Medical Science, 2019)
Background: Lupus anticoagulants (LA) are in vitro inhibitors paradoxically associated with thrombosis and performing coagulation test on a mixture of test plasma and pooled normal plasma to evidence this property is a mainstay in LA detection. Case report: We report a 20-year-old man who presented with one week history of fever, associated with productive cough, jaundice, and lethargy. He was a known case of systemic lupus erythemathosus for 10 years. Isolated activated partial thromboplastin time (APTT) were prolonged. Interestingly, the APTT mixing study was not corrected and showed more prolonged results than baseline APTT. LA study showed presence of a strong LA, which is related to the underlying autoimmune disease. Discussion: This case focuses on the ‘rebound phenomenon’ in APTT mixing test, from a strong LA that gives a cofactor inhibitory effect to the entire test system after adding the normal plasma. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.430-433